IDENTIFIKASI SPESIES DERMATOFITA PENYEBAB TINEA CAPITIS PADA SANTRIWATI DI PONDOK PESANTREN - IMELDA PUTRI KUSHARYATI; Qurrotu A’yunin Lathifah; Andyanita Hanif Hermawati (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Dermatophytes are a classification of fungi that attack and damage keratinized tissue, including hair, skin, nails, and fur. The cause of this infection is keratinolytic filamentous fungi referred to as dermatophytes. Islamic boarding schools are often at risk of dermatophyte transmission, with warm and humid environments accelerating fungal growth in female students. Tinea capitis is a dermatophytosis that infects hair follicles and can cause hair loss and scaly lesions. The purpose of this study was to determine whether dermatophyte species cause Tinea capitis infections in female students. The method used was analytical observation with a cross-sectional design. The sampling technique used was non-probability sampling with a purposive sampling method. The results of the study with 20 respondents tested positive for dermatophyte fungi, 10 respondents and 10 respondents tested negative. In conclusion, the identification of dermatophyte fungi obtained Trichophyton mentagrophytes and Trichophyton rubrum species in positive results. In negative results, non-dermatophyte fungi were found.